Transcending the Monitor: Investigating the Streamer-Audience Dynamic and its Effect on Streaming Consumption Preferences - Palomino-Flores, Paola (2024)
In the context of changing social dynamics reshaping media consumption, the focus turns to the intriguing realm of streaming. This study encompasses the perspectives of consumers and creators, unveiling the construction of effective communication between streamers and their audience, and how this interaction influences preferences and consumption habits. Through a mixed methodology, combining a questionnaire for 205 consumers and interviews with 21 streamers, significant findings emerge. The interaction between streamers and their audience not only guides content creation and sharing but also forges a virtual community transcending boundary. This study underscores that streaming is more than entertainment—it’s a cultural phenomenon redefining how we connect with content and each other. Ultimately, it is concluded that interaction and content, in a symbiotic process, originate from streamers, adapting to the themes and desires of a captive audience.